Shikhara (superstructure) of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
According to the Archaeological Survey of India (ASI), the Hazareshwar Temple is classified as being constructed in the Bhumija style. However, upon closer examination of the shikhara (superstructure), it is evident that it does not adhere strictly to the typical Bhumija style but rather exhibits a mixed style. The mulamanjri (principal spire), uruh shringas (subsidiary spires leaning against the main spire), and kutas (miniature shrines) represent a feature of shekhari shikhara style i.e., the central latina spires with rows of half spires added on either side. Pediments are present on all three sides, with surasenakas situated above them. Divinities such as Brahmani, Brahma, and Shiva are carved on the pediments above the antarala and garbhagriha. Notably, the surasenaka features a stunning depiction of Natesha.